2021
DOI: 10.1007/s00894-021-04752-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational structural, electronic and optical properties of the palmitic acid in its C form

Abstract: In this work, we report a theoretical study of the structural, electronic, and optical properties of palmitic acid crystal in its C form under DFT calculations level. Palmitic acid is a fatty acid that constitutes the large majority of vegetable oils with recognized potential applications in medicine, pharmaceuticals, cosmetics technology, foods, and fuel. As a main result, we have found that the electronic bandstructure reveals indirect gap 3.713 ( −→ and −→ Γ), as a main bandgap, while the secondary bandgaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[4][5][6][7] Furthermore, structural and kinetic studies revealed that these compounds can inhibit phospholipase A(2), thus being an anti-inammatory agent. 8,9 According to the literature, 10,11 these compounds can be used to gra polymers and produce carriers for non-viral gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Furthermore, structural and kinetic studies revealed that these compounds can inhibit phospholipase A(2), thus being an anti-inammatory agent. 8,9 According to the literature, 10,11 these compounds can be used to gra polymers and produce carriers for non-viral gene delivery.…”
Section: Introductionmentioning
confidence: 99%